2007
DOI: 10.1111/j.1468-2389.2007.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Candidates' Ability to Identify Criteria in Nontransparent Selection Procedures: Evidence from an assessment center and a structured interview

Abstract: In selection procedures like assessment centers (ACs) and structured interviews, candidates are often not informed about the targeted criteria. Previous studies have shown that candidates' ability to identify these criteria (ATIC) is related to their performance in the respective selection procedure. However, past research has studied ATIC in only one selection procedure at a time, even though it has been assumed that ATIC is consistent across situations, which is a prerequisite for ATIC to contribute to selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
88
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 48 publications
6
88
1
Order By: Relevance
“…Correlations are typically in the low to moderate range, and although it appears to be more strongly associated with verbal than nonverbal ability (Melchers et al, 2009), a recent study (Melchers et al, 2012) found even verbal ability only related at r = .17. In addition, Konig et al (2007) demonstrated that ATIC explained incremental variance in selection test performance over and above cognitive ability.…”
Section: Cognitive Abilitymentioning
confidence: 96%
See 4 more Smart Citations
“…Correlations are typically in the low to moderate range, and although it appears to be more strongly associated with verbal than nonverbal ability (Melchers et al, 2009), a recent study (Melchers et al, 2012) found even verbal ability only related at r = .17. In addition, Konig et al (2007) demonstrated that ATIC explained incremental variance in selection test performance over and above cognitive ability.…”
Section: Cognitive Abilitymentioning
confidence: 96%
“…It includes person perception, social insight, and interpersonal awareness. Konig et al (2007) described ATIC as a specific component that would also fit within this domain.…”
Section: Social Understandingmentioning
confidence: 97%
See 3 more Smart Citations